Intelligent Correction and Monitoring of Ship Propulsion Rotary Device Vibration - Ou, Chao-Hui; Ting, Kuo-Huan; Lee, Nien-Tsung; Shih, Wu-Chiao (International Journal of Engineering and Technology Innovation, 2022)
Field inspection is a traditional way to detect the problem of shaft imbalance or abnormal vibration in a ship propulsion system; however, the ship cannot execute any tasks or activities during calibration. This study develops a human-machine monitoring interface (HMMI) to estimate vibration abnormalities and implement an intelligent active balance correction to the propulsion system online. In this study, Arduino IDE, InduSoft, and LabVIEW are used to create a function monitored by HMMI. By comparing the abnormal vibration amplification of the moment of inertia, HMMI calculates the correct mass to reduce the vibration. The experimental results show that, after HMMI carries out continuous active balance correction online, the correction rate achieves 105.37%. This indicates that HMMI can calculate the amount of imbalance and phase angles and drive a counterweight to the correct balance position while the device is still operating.